Building Maintenance and Repair: Determining the Workforce Demand and Supply for a Mandatory Building-Inspection Scheme - Sing, C.; Chan, H.; Love, Peter; Leung, A. (American Society of Civil Engineers, 2016)
To deal with the existing building dilapidation problem in Hong Kong, a mandatory building inspection scheme (MBIS) has been introduced. The effectiveness of the scheme is reliant on an adequate supply of registered inspectors (RIs) to inspect and supervise repair works. To ensure that there is an adequate supply and demand of RIs to enable the implementation of the MBIS, a robust workforce planning model is proposed. The database of private buildings from the Hong Kong Home Affairs Department and a web-based survey were used to collect qualitative and quantitative data, from practitioners and professional bodies, to determine the demand and supply of labor. A quantitative modeling approach, which utilizes a labor multiplier method, revealed that there will be a shortage of RIs to meet future professional workforce demand under the MBIS. The qualitative aspect of the research reported in this paper, which addressed the perception of eligible RIs, revealed that the majority of respondents were disinterested with becoming an RI as their responsibility and liability had not been clearly defined under the current MBIS scheme. The findings provide the local government authority with the ability to visualize the workforce demand under the MBIS and articulate future workforce strategy to ensure an adequate supply of the professional workforce.As a result, the condition of buildings and the living environment of the general public will be improved with the implementation of MBIS to safeguard public safety.